Nurses perceptions and use of artificial intelligence in healthcare - Hossein Namdar Areshtanab; Farnaz Rahmani; Maryam Vahidi; Seyyedeh Zahra Saadati; Akram Pourmahmood (Scientific Reports)
Abstract The integration of artificial intelligence (AI) in nursing care is an important professional issue. However, few studies have investigated the knowledge, attitudes, application, and acceptance of artificial intelligence in nursing care. This study aimed to explore the knowledge, attitude, application, and acceptance of artificial intelligence in health care among Iranian nurses. A descriptive design conducted on 400 nurses who worked in university hospitals in Tabriz, Iran in 2024. A stratified random sampling method was used for selecting participants. Data collection tools included a demographic-social questionnaire and questionnaires of knowledge, attitude, application, and acceptance towards artificial intelligence in nursing care. Data were analyzed using both descriptive and inferential statistics. The results of the study showed that most nurses (41.1%) had low knowledge, (65.8%) good attitude, (74.6%) a moderate level of acceptance and (55.8%) applied AI at a high level. There was a positive and significant correlation between nurses’ knowledge and their attitude (R = 0.311, P < 0.001), application (R = 0.514, P < 0.001), and acceptance (R = 0.381, P < 0.001) regarding AI. The study’s results showed that nurses have low knowledge about AI, which shows the need to hold training workshops on this subject. The study’s results also showed that nurses have positive opinions of AI in the healthcare industry, which will help them speed up procedures and improve nursing care.